Diabetes mellitus als prognostischer Marker beim Oropharynx- und Larynxkarzinom = Diabetes mellitus as a prognostic marker in oropharyngeal and laryngeal squamous cell carcinoma - Plath, Karim; Doll, Josef; Federspil, Philippe A.; Plinkert, Peter K.; Heß, Jochen (HNO, 2016)
Recent experimental and clinical studies have provided compelling evidence that diabetes mellitus (DM) is an important risk factor in various cancers, and may affect both pathogenesis and prognosis. Additionally, antidiabetic agents such as metformin exhibit an antitumorigenic effect. However, to date there is insufficient knowledge about the role of DM in the pathogenesis and prognosis of head and neck squamous cell carcinoma (HNSCC).In a retrospective monocentric study including 424 patients with SCC of the oropharynx (OPSCC) or larynx (LaSCC), the impact of DM on clinical and histopathologic parameters was investigated. The authors found a rising incidence of DM among LaSCC patients (<10 % until 2005 and 20 % since 2006) and a significant association between DM and clinical and histopathologic features (age, gender, tumor size, and pathologic grading), which depended on the anatomic site. Moreover, a clear trend toward unfavorable progression-free and overall survival of HNSCC patients with DM upon current treatment modalities was evident.The presented data support a relative increase in patients with DM, particularly for LaSCC. This might have a sustained influence on treatment decisions and management, and should be considered in future clinical trials. A better understanding of the cellular and molecular traits of HNSCC in DM could pave the way for innovative therapeutic strategies in terms of personalized medicine.
Gesehen am 01.02.2018